FEATURES OF USING DISTANCE LEARNING TECHNOLOGIES IN TEACHING FOREIGN LANGUAGES AT UNIVERSITY: ANALYSIS OF EXPERIENCE (Proceedings of Southern Federal University. Philology, 2023)
DOI 10.18522/1995-0640-2023-1-145-157Abstract. A lot of attention is paid to distance learning today, as, probably, none of the many ways of learning using technology. Modern research in education, and in particular in ICT, tends to use technological resources to the maximum and use them effectively in pedagogy. In the field of foreign language teaching, much has been done to cover various languages of the world, but attempts are constantly being made to find new solutions, taking into account the specific needs of language learners. The purpose of the article is to present the technological aspect of the DE system common to all courses, to identify the main features of teaching a foreign language in distance learning, to consider the process of developing and implementing online English courses from the point of view of the overall design of the course, the choice of teaching materials, technological and pedagogical processing of course materials, the role of the teacher, support and motivation of students.Key words: distance learning, foreign language, communication, technology, education, integration, digital generation